De-presentation rights as a response to extremism. Issue 3 (3rd May 2016) - Malkopoulou, Anthoula
Abstract : Due to the persistent rise of extremism, democrats in recent years have been exploring old and new possibilities of democratic self-defence. This article explores an unconventional and little known alternative to militant democracy that places the demos at the centre stage of the struggle against extremism. Through a neo-procedural reinterpretation of ancient ostracism and modern-day recall, I suggest that citizens should have rights of democratic de-selection of elected parties and candidates. I argue that, if properly designed, such a mechanism of de-presentation distributes the burden of democratic self-defence among citizens and creates a bottom-up majoritarian resistance to anti-democratic threats, without compromising free parliamentary mandate or minority rights.